Cloning and Characterization of a Flavonol Synthase Gene From Litchi chinensis and Its Variation Among Litchi Cultivars With Different Fruit Maturation Periods - Liu, Wei; Xiao, Zhidan; Fan, Chao; Jiang, Nonghui; Meng, Xiangchun; Xiang, Xu (Frontiers in Plant Science, 2018)
Litchi (Litchi chinensis) is an important subtropical fruit tree with high commercial value. However, the short and centralized fruit maturation period of litchi cultivars presents a bottleneck for litchi production. Therefore, development of novel litchi cultivars with extremely early fruit maturation period is critical for the litchi industry. Previously, we identified that the genotypes of extremely early-maturing (EEM), early-maturing (EM), and middle-to-late-maturing (MLM) cultivars at a specific locus SNP51 (substitution type, C/T) were consistent with their respective genetic background at the whole-genome level; a homozygous C/C genotype at SNP51 systematically differentiated EEM cultivars from others. The litchi gene on which SNP51 was located was annotated as flavonol synthase (FLS) that catalyzes the formation of flavonols. Here, we further elucidated the variation of the FLS gene from L. chinensis (LcFLS) among EEM, EM and MLM cultivars. EEM cultivars with a homozygous C/C genotype at SNP51 all contained the same 2199 bp sequence of LcFLS gene. For MLM cultivars with a homozygous T/T genotype at SNP51, the sequence length of LcFLS gene ranged from 2202 bp to 2222 bp. All EM cultivars with a heterozygous C/T genotype at SNP51 contained two different alleles of LcFLS gene; a 2199 bp sequence identical to that in EEM cultivars and a 2205 bp sequence identical to that in MLM cultivar ‘Heiye’. Moreover, the coding regions of LcFLS gene of other MLM cultivars were almost identical to that of ‘Heiye’. Therefore, the LcFLS gene coding region could be used as a source of diagnostic SNP markers to discriminate or identify genotypes with the EEM trait in litchi. The expression pattern of LcFLS gene and accumulation pattern of flavonol from EEM, EM, and MLM cultivars were analyzed and compared using qRT-PCR and HPLC for mature leaves, flower buds, and fruits at 15, 30, 45, and 60 days after anthesis. Our results indicated that flavonol contents and LcFLS gene expression levels were positively correlated in the three cultivars and both decreased from the EEM to MLM cultivars, with moderate levels in the EM cultivars. The LcFLS gene function could be further analyzed to elucidate its correlation with phenotype